Open reduction and internal fixation for Mason type III radial head fractures: Is it different from that for Mason type II fractures?. (27th September 2018) - Lee, Yong-Suk; Kang, Young-Hoon; Chung, Yang-Guk; Shin, Seung-Han
Purpose: The objective of this study was to investigate whether the outcomes of Mason type III radial head fractures (RHFs) treated by open reduction and internal fixation (ORIF) were comparable to those of Mason type II RHFs treated by ORIF. Methods: A total of 87 surgically treated RHF patients were reviewed. Their fractures were Mason type II in 39 patients (all treated by ORIF) and Mason type III in 48 patients (40 treated by ORIF, 7 by radial head arthroplasty, and 1 by resection). Although ORIF was preferred for Mason type III RHFs in our series, an arthroplasty was performed when the fracture accompanied severe associated injuries or multiple traumas. Radiological and functional outcomes were evaluated and complications were reviewed. Results: When Mason type II and Mason type III in general were compared, QuickDASH score, a shortened version of the Disabilities of the Arm, Shoulder and Hand (DASH) score, and forearm rotation were significantly worse in Mason type III. However, when comparing Mason type II and Mason type III treated by ORIF in which the proportion of associated injuries were not significantly different, there was no significant difference in QuickDASH score, range of extension/flexion, or complication rate. Forearm rotations were significantly more limited in Mason type III treated by ORIF (7° for pronation and 7° for supination), and Mason type had an independent effect on forearm rotations in multivariate analysis. Conclusion: ORIF for Mason type III fractures with low level of associated injury can be as good as that for Mason type II fractures, except for less forearm rotation.